2021
DOI: 10.3390/md19040213
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Prebiotic and Anti-Colon Cancer Activities of Agar-Derived Sugars from Red Seaweeds

Abstract: Numerous health benefits of diets containing red seaweeds or agar-derived sugar mixtures produced by enzymatic or acid hydrolysis of agar have been reported. However, among various agar-derived sugars, the key components that confer health-beneficial effects, such as prebiotic and anti-colon cancer activities, remain unclear. Here, we prepared various agar-derived sugars by multiple enzymatic reactions using an endo-type and an exo-type of β-agarase and a neoagarobiose hydrolase and tested their in vitro prebi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…It is speculated that this effect may be related to biologically active agarose components enriched from red seaweed. Upregulation of caspase-3, Bax, and caspase-9 expression and downregulation of Bcl-2 and Bcl-xL were observed in HCT-116 cells after AHG treatment (30). Therefore, the growth of human colon cancer HCT-116 cells was effectively suppressed by AHG, indicating that AHG is a potential alternative as an anti-CRC agent.…”
Section: Agarosementioning
confidence: 90%
“…It is speculated that this effect may be related to biologically active agarose components enriched from red seaweed. Upregulation of caspase-3, Bax, and caspase-9 expression and downregulation of Bcl-2 and Bcl-xL were observed in HCT-116 cells after AHG treatment (30). Therefore, the growth of human colon cancer HCT-116 cells was effectively suppressed by AHG, indicating that AHG is a potential alternative as an anti-CRC agent.…”
Section: Agarosementioning
confidence: 90%
“…Recently, it was demonstrated that in addition to B. infantis ATCC 15697, other probiotic Bifidobacterium strains assimilating HMOs also have an agarolytic β-galactosidase activity 43 . Second, this unique microbial symbiosis between two distinct gut bacteria, B. plebeius and B. infantis , enables the production of AHG, a rare sugar possessing various physiological activities 23 , 43 , through the degradation of seaweed agarose (Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…B. infantis ATCC 15697 is isolated from the intestine of infant ( https://www.atcc.org/products/15697 ) where HMOs are abundant, and it is known as a typical member of the gastrointestinal microbiota of breastfed infants 44 . Furthermore, for the cultivation of B. infantis ATCC 15697 , HMOs such as lacto- N -tetraose, lacto- N -neotetraose, and 2′-fucosyllactose, are the preferred carbon sources than AgaDP3 in terms of cell growth rate and maximum cell density measured at OD 600 43 , 45 ; this implies that Bga42A and Bga2A participate in the degradation of HMOs 40 and AgaDP3, but they favorably degrade HMOs than AgaDP3.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive compounds have also been found in polymers from red seaweeds. Some of the properties are antioxidant activity [13], prebiotic activity [14] and others. In this context, biomedical applications such as anti-inflammatory activity [15], antiviral activity [16], antibacterial activity [17], antimicrobial activity [18] and antitumoral activity [14], among others, [1] have been reported; particulate systems with biomedical applications could also be another possibility for delivering compounds that are of in this field [19,20].…”
Section: Introductionmentioning
confidence: 99%